PENGGUNAAN E-COMMERCE DALAM PENGEMBANGAN SEKTOR UMKM - Muarrif, Zul Ihsan (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2022)
UMKM are one of the pillars of the Indonesian economy, but the dilemma is the minimal use of technology by UMKM amid ongoing global competition. This study aims to provide awareness to both UMKM and stakeholders about the importance of using technology in advancing the economy. The method used is literature study with reference sources from several articles available online. The results showed that there was still a lack of interest in the use of technology coupled with inadequate facilities. So it can be concluded that there are still many UMKM in areas that still use traditional methods. The author suggests to increase the supporting facilities by stakeholders for the sustainability of the welfare of the small community.